Song of the Coastlands & Come on America to Treasure Isle - Harry A. Powell::::::::: (Strathmore Press)
Piano and vocal score, 3 p. On cover: Photo of Treasure Island, various views of the San Francisco bay area within. Lyrics also printed separate from music on pages 8 and 9 c1938 by J.B. Chapman